Hernia Ventralis - Felicia Adelina Shannen; I Made Adi Surya Wijaya; Ida Bagus Yudha Prasista (Cermin Dunia Kedokteran, 2021)
Hernia ventralis merupakan penonjolan isi rongga abdomen pada dinding abdomen. Seorang wanita, 54 tahun, datang dengan keluhan utama benjolan perut sejak kecil. Pada pemeriksaan didapatkan massa bulat diameter 10 cm di abdomen regio epigastrika, membesar pada posisi berdiri dan duduk serta mengecil saat berbaring. Pada pasien dilakukan operasi primary open repair pada defek hernia ventralis. Ventral hernia is a protrusion of abdominal cavity contents in the abdominal wall. A 54 year-old female presented with a lump in the stomach since childhood. On examination, a round mass measuring 10 cm in diameter was found in the abdominal epigastric region, enlarged in standing and sitting positions and reduced when lying down. Primary open repair was performed on the ventral hernia defect.